Modelling caregiving interactions during stress - Ab. Aziz, Azizi; Treur, Jan; Van Der Wal, C. Natalie (Springer Berlin Heidelberg, 2010)
Few studies describing caregiver stress and coping have focused on the effects of informal caregiving for depressed care recipients.The major purpose of this paper was to investigate the dynamics of the informal care support and receipt interactions among caregivers and care recipients using a computational modelling approach.Important concepts in coping skills, strong ties support networks and stress buffering studies were used as a basis for the model design and verification.Simulation experiments for several cases pointed out that the model is able to reproduce interaction among strong tie network members during stress.In addition, the possible equillibria of the model have been determined, and the model has been automatically verified against expected overall properties.